METHODOLOGY OF PRACTICE-ORIENTED RESEARCH ACTIVITIES OF STUDENTS DURING PEDAGOGICAL INTERNSHIP: BUILDING NATIONAL IDENTITY IN MULTICULTURAL ENVIRONMENT - Tatyana L. Oskolova (Russian State Vocational Pedagogical University, 2015)
The aim of the article is to develop integrated practice-orientedresearch assignments for students - upcoming teachers for the period of teaching practice. Proposed investigation is based on formal requirements of national education including analysis of specific educational activities in ethnically and culturally diverse society.Methods. Axiological and anthropological approaches are used as the methodological basis of the study that reveal value and meaning of multicultural education and focus on development of multicultural personality of students in the learning process at the university. The work contains theoretical analysis of the Russian Federation State Program «Development of Education» for 2013-2020.Results. The characteristics of culturally sensitive and culturally insensitive teaching technology are given in the article. Pedagogical factors of building tolerant environment which enables friendly interaction of multicultural students are revealed. Technology of multicultural teaching aimed at humanistic positive transformation of students' personality and educational environment embracing cultural diversity is suggested.Scientific novelty. The concept «practice-orientation of education» is offered to define as the ability to establish links between the teachers' knowledge, skills and significant social and personal problems of students. In the context students' research activity, practice-orientation is supposed to involve the study of working with students in a diversified environment taking into account their cognitive, ethno-cultural, linguistic differences, degree of tolerance towards peers and the level of intercultural competence.Practical significance. Basic algorithm of teacher's work in a multicultural environment is proposed. The algorithm is based on the following uniting values: caring for others and compassion; striving for success by fair means; honesty and integrity; team spirit; respect of other opinions; responsibility for own words and deeds; understanding, tolerance and acceptance of the world around. International communicative Internet project is developed including criteria for assessment of social and students' personal characteristics as a result of the project work.